A beautiful day in these neighborhoods: variations in access to school, food, and healthcare in neighborhoods along an urban to rural gradient - Carver, Rial Tombes (Kansas State University, 2019)
Neighborhoods are fundamental units of planning. Over the past century, planners have presented theories on designing the ideal neighborhood. Many of these theories include recommendations for size, population, and orientation to basic amenities like food, healthcare and education. Most neighborhood level research has paid little attention to the contexts (urban, suburban, and rural) that neighborhoods are situated. The purpose of this research is to explore the differences in neighborhood forms, characteristics, and access to basic needs (food, healthcare and education) along an urban to rural gradient. Specifically, this study aims to (1) explore contextual factors in neighborhood characteristics and access to basic needs of the neighborhood, and (2) identify patterns in people’s perceived neighborhood center and boundaries and (3) identify patterns in access to basic needs (food store, primary health care, and school) from selected neighborhoods along an urban to rural gradient in the Wichita, Kansas, metropolitan area. This study uses surveys as a primary data collection method and cognitive mapping in order to capture data on neighborhood characteristics and travel patterns to basic needs. Descriptive statistics, cross tabulations, ANOVAs and geo-spatial analysis are used to analyze the results. Results indicate that variations in neighborhood perceptions along the urban to rural gradient exist and they are more prevalent than variations in travel patterns along the urban to rural gradient. Neighborhoods along the urban to rural gradient are distinct, but suburban and rural neighborhoods appear to be more alike than suburban and urban. The need for a definition of suburban is evident. Planners often use neighborhoods as a unit for developing plans. This research provides insight that informs and improves future neighborhood level planning efforts.
Keywords: Neighborhood Planning; Access to Basic Needs; Urban to Rural Gradient; Transect Planning; Neighborhood; Urban Context